(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2012)
The design of micromotor for electromechanical discrete polarizing reflective phase shifter for phased arrays of centimeter and millimeter bands is offer. The stator of the micromotor consists of two sections of the electromagnets, which are located between the rotor with permanent magnets. In one step the rotor engine can be rotated by an angle of ±45° or ±90°, which corresponds to phase shifts of 90°, 180° and 270°. Time for turning the rotor to one of the operational corners is (5/6) ms at the lowest possible energy costs. Experimentally tested and measured the basic parameters of the micromotor: the time change and energy costs for the phase shift; established the dependence of the rotor rotation at given angle and energy consumption for changing one discrete of phase shift as function of the voltage pulse that applied to the stator of the micromotor.